Reimagining the role of teaching-focused faculty in research-intensive universities: The evolution of scholarly expectations and departmental influence - Alex R. Paine; Mike Wilton; Sabrina M. Solanki; Marina Ellefson; Julie E. Ferguson; Stanley M. Lo; Brian K. Sato (PLoS ONE, 2025)
Research-intensive universities aim to conduct cutting-edge research while providing the knowledge and skills necessary to prepare students to excel in their respective fields. As student enrollments surge, many institutions have turned to hiring teaching-focused faculty. In the University of California (UC) system, there exists a unique position known as the Professor of Teaching (PoT). This position is tenure-eligible, and members are required to engage in classroom teaching, scholarly activities, and service responsibilities. To shed light on the background characteristics, roles and perceptions of the impact of teaching-focused faculty in research-intensive institutions, we collected survey data from STEM PoT faculty across the UC system. We employed a mixed methods approach, using descriptive and inferential statistics to analyze quantitative responses and thematic analysis to examine open-ended qualitative data. Our analysis shows that pre-tenure PoTs place greater emphasis on scholarly activities relative to their peers who have been in the role for longer. However, their training and the institutional resources provided may not align with expectations for scholarly activities. Additionally, we find that PoTs who engage in research perceive that they have a more significant impact on their colleagues’ teaching. This finding underscores the value of research, even for teaching-focused faculty. This study informs the evolving landscape of teaching-focused faculty within research-intensive universities and provides recommendations for administrators considering how to ensure that their institutions are fulfilling their educational mission.